Chance favors the prepared mind – Exploring angles and aspects of Turku (New Performance Turku Festival 2021) - Karuvuori Maire; Parkkinen Marjukka (My University, 2022)
Chance observes the environment’s effect on survival. It searches options to the threat and emergency focused media through art, science and community. The three part work is a collaboration between artist Maire Karuvuori and futures researcher Marjukka Parkkinen who both have researched survivalism.
During the first part Karuvuori explores preparednes by camping in Turku and its surroundings. In the second part the experiences, field recordings and reflection deepen into a sound work, a dialogue between Karuvuori and Parkkinen. The recording will be added to our website during the festival.
The third part is an explorative walk at the center of Turku. We observe and discuss surviving as something personal and communal, but perhaps also societal or planetary phenomenon.